2021
DOI: 10.1186/s12936-020-03539-4
|View full text |Cite
|
Sign up to set email alerts
|

Widespread zoophagy and detection of Plasmodium spp. in Anopheles mosquitoes in southeastern Madagascar

Abstract: Background Malaria is a top cause of mortality on the island nation of Madagascar, where many rural communities rely on subsistence agriculture and livestock production. Understanding feeding behaviours of Anopheles in this landscape is crucial for optimizing malaria control and prevention strategies. Previous studies in southeastern Madagascar have shown that Anopheles mosquitoes are more frequently captured within 50 m of livestock. However, it remains unknown whether these mosquitoes prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The low prevalence of fed females (12.9%) reported in this study compared to gravid females (49.1%), supports the assumption that mosquito collection for blood meal analysis is mainly affected by the resting position especially after taking the blood meal [ 42 ]. Recently, a study conducted by Finney et al indicated that most of the human blood meals were from Anopheles mosquitoes trapped outdoors, while many livestock blood meals were from Anopheles mosquitoes trapped indoors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low prevalence of fed females (12.9%) reported in this study compared to gravid females (49.1%), supports the assumption that mosquito collection for blood meal analysis is mainly affected by the resting position especially after taking the blood meal [ 42 ]. Recently, a study conducted by Finney et al indicated that most of the human blood meals were from Anopheles mosquitoes trapped outdoors, while many livestock blood meals were from Anopheles mosquitoes trapped indoors [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results disagree with a previous report from Burkina Faso, where human blood meal source was more than 80% [ 47 ]. However, this variation can be as a result of host availability in that specific region [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported mosquitoes infected by Plasmodium spp. in Africa [ 59 , 60 , 61 , 62 ] and the Amazon Basin in South America [ 47 , 51 , 55 ] where higher rates of transmission have been reported. The absence of infected mosquitoes was not unexpected due to the low number of malaria cases reported in Gracias a Dios, Bay Islands, and El Paraíso, during the years of collection (average of 380, 7, and 18 cases per year, respectively), and the absence of malaria cases in Cortés and Comayagua.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many P. vivax vectors are early biters and outdoor feeders and exhibit outdoor-resting patterns [ 68 ]. These characteristics are supposed to make it easier to get through control measures such as insecticide-treated nets (ITNs) or indoor residual spray (IRS).…”
Section: Introductionmentioning
confidence: 99%